SPECIALIZATION IN HADITH (TAKHASSUS AL-HADITH) AT ISLAMIC STUDIES INSTITUTION IN INDIA - Ahmad Shah, Faisal; Ghazali, Mohd al’Ikhsan (Journal of Al-Tamaddun, 2014)
This article discusses regarding the development of takhassus hadith programme practiced in Darul ?Ulum Deoband, Jamiah Mazahir al-?Ulum and Jamiah Sanabil. This article aims to analyze takhassus hadith syllabus used in this three Islamic institutions, its strength and weakness and the best methodology which can be adapted in the study of Hadith. The findings of this research show that takhassus hadith programme offered in these three Islamic institutions prove the rapid development of hadith studies in India. Some of the advantages the students obtained in this area are the combination of practical and theoritical lesson. They are exposed to theoretical study of hadith literatures such as turath as well as practical trainings in the subjects learned especially in the field of takhrij hadith, dirasat al-asanid and rijal knowledge.